Recurrent primary orbital well-differentiated liposarcoma /atypical lipomatous tumor: A rare case report with six-year follow-up - Frank Mei; Lin He; Parsha Forouzan; Ronald Mancini; Robert Nick Hogan (American Journal of Ophthalmology Case Reports, 2022)
Purpose: We report a case with over 6 years of follow-up for well-differentiated liposarcoma or atypical lipomatous tumor (WDL/ALT). Observations: Over a 6-year time course, a patient with a recurrent right orbital mass was biopsied/debulked four times. It was not until the fourth biopsy that a diagnosis of WDL/ALT was obtained. Throughout the time course, the patient maintained good vision and there has been no evidence of dedifferentiation or metastasis thus far. Conclusions: The diagnosis of WDL/ALT sound be considered in the cases of a recurrent orbit mass when pathology continually shows nonspecific fibrofatty tissue with chronic inflammatory changes.